Orientalism, its concept, origin, development, motives, and goals With analysis and criticism of the Orientalists' opinions (Journal of the College of Basic Education, 2023)
Orientalism is considered one of the most dangerous counter phenomena to which Islam and the Arabs have been exposed throughout history.humanity and its different stages, and that there were few Orientalists who did justice to Islam and the Arabs intheir writings, and that the sects of different nations varied in their cultures, languages, values, andHer word and her goals were unified to focus on studying a religion that she does not believe in and a people that do not know much.You do not want to know the truth from falsehood, rather you want to distort Islam and Arabism.and its splendid human civilization, and the campaigns that Islam was subjected to by manyThe orientalists aimed mainly at distorting and casting doubt on the tolerant doctrine of Islam and trying toTo alienate people from embracing that belief and thus stop its spread, hence the seriousness of what he adopts.Orientalists from their research when they study Islam, ideas, culture and civilization intellectuals ask usThe necessity of vigilance, caution, and attention to everything that these people write, and sorting out what is correct, so we encourage it.We reject what is false, so we expose it and respond to it. In this study, we will deal with Orientalism and its concept., its origins and development, its goals and motives, with a presentation and analysis of the opinions of some orientalists, we ask God toIt helps us in our humble effort as a serious and sincere addition to all the researchers who contributed to the writing.about Orientalism.